The Role of ‘Spirituality’ in Religion-secular Relational Discourse: The Case of Yoga in Britain - Vollmer, Laura J. (Journal of religion in Europe, 2020)
Abstract This article examines the ‘relational etymology’ of the term ‘secular’ relative to ‘religion’ and the role of the concept ‘spirituality’ in discursive change. Employing a relational methodology to the sociology of knowledge approach to discourse analysis, concept formation and transformation of these terms is considered as a specific matter of how the terms are positioned relative to one another in the discourse. It is found that while ‘spirituality’ first worked on the side of ‘religion’ to differentiate it from the ‘secular,’ it was later differentiated from ‘religion’ and placed in ‘secular’ discourse. This is exemplified with the case of yoga in Britain. Implications for the religion-secular relationship and the secularization thesis are explored.